Clinical characteristics and surgical management of endometriosis‐associated infertility: A multicenter prospective cohort study. Issue 1 (18th February 2022) - Bhurke, Aishwarya V.; DasMahapatra, Pramathes; Balakrishnan, Sheila; Khan, Shagufta A.; Mortlock, Sally; Das, Vinita; Chellamma, Nirmala; Cheruvara Vadakkathil, Sowmini; Srivastava, Aarti; Majumdar, Amiya; Pasi, Achhelal; Sachdeva, Geetanjali; et al.
Abstract: Objective: To study clinical, surgical characteristics and the relationship between endometriosis lesion types and conception rate after surgery in infertile women with endometriosis. Methods: A prospective, multicenter cohort of 204 women (age 20–35 years) with endometriosis was followed up post‐surgery between November 2017 and February 2020 at three tertiary‐care hospitals. Results: Based on the severity of endometriosis lesion type, deep infiltrating endometriosis (DIE) (81/204, 39.7%) was the most common lesion; followed by ovarian endometriosis (OMA) (64/204, 31.4%), and superficial peritoneal endometriosis (SUP) (59/204, 28.9%). Endometriosis patients had a single lesion type (94/204, 46.1%), two lesion types (77/204, 37.7%), or three lesion types (33/204, 16.2%) with significant differences between regions ( P  < 0.001). Around 40% (37/95) of obese women had SUP ( P  = 0.003) whereas 78% (14/18) of underweight women had DIE ( P  < 0.001). Significant differences in mean Endometriosis Fertility Index scores between endometriosis lesion types and patients with one, two, and three types of lesions were observed ( P  < 0.001). The majority (22/32, 68.8%) of the women conceived naturally after the surgery. Half (16/32; 50%) of the women with a single lesion type conceived after the surgery; of which most (13/16, 81.2%) had SUP, followed by OMA (2/16, 12.5%), and DIE (1/16, 6.3%). Conclusion: Women with SUP and only one type of endometriotic lesion were more likely to conceive post‐surgery. Abstract : The contents of this page will be used as part of issue TOC only. It will not be published as part of main article. Women diagnosed with superficial peritoneal endometriosis lesions and only one type of endometriotic lesion are more likely to conceive after surgery.